AN ANALYSIS OF LANGUAGE EXPRESSIONS FOCUS IN “WHEN ENGLISH RINGS A BELL” FOR JUNIOR HIGH SCHOOL STUDENTS YEAR VIII - Simbolon, Masliana; Nadeak, Lasmaida; Batu, K. H. L.; Situmorang, Nursitta; Saragih, Erikson (Jurnal Pendidikan Bahasa Inggris undiksha, 2020)
This study aims to describe of expressions  that used  by students contained in “When English Rings a Bell” textbook of eighth grade students. The expressions used by the  speakers to express a massage, thoughts, feelings, or opinions to other people. People must use certain expression depend on the situation. This study used qualitative research design because all the data get from words not numbers. The writers used conversation from the book as a source of the data. The result of the study shows that the expressions contained in textbook When English Rings A Bell fits with the situation, what and when they want to speak.  The kinds of expressions can be conveyed through expression in this study is how to ask and give attention.